Non-GM Genome Editing Approaches in Crops - Gong, Zheng; Cheng, Ming; Botella, Jose R. (Frontiers in Genome Editing, 2021)
CRISPR/Cas-based genome editing technologies have the potential to fast-track large-scale crop breeding programs. However, the rigid cell wall limits the delivery of CRISPR/Cas components into plant cells, decreasing genome editing efficiency. Established methods, such as Agrobacterium tumefaciens-mediated or biolistic transformation have been used to integrate genetic cassettes containing CRISPR components into the plant genome. Although efficient, these methods pose several problems, including (1) The transformation process requires laborious and time-consuming tissue culture and regeneration steps; (2) many crop species and elite varieties are recalcitrant to transformation; (3) The segregation of transgenes in vegetatively propagated or highly heterozygous crops, such as pineapple, is either difficult or impossible; and (4) The production of a genetically modified first-generation can lead to public controversy and onerous government regulations. The development of transgene-free genome editing technologies can address many problems associated with transgenic-based approaches. Transgene-free genome editing has been achieved through the delivery of preassembled CRISPR/Cas ribonucleoproteins, although its application is limited. The use of viral vectors for delivery of CRISPR/Cas components has recently emerged as a powerful alternative but it requires further exploration. In this review, we discuss the different strategies, principles, applications, and future directions of transgene-free genome editing methods.